CRITICAL AREAS IN OPERATION OF CITY PUBLIC TRANSPORT (Perner's Contacts, 2011)
City public transport in the Czech Republic operates in all large cities.We recognize the subsystem bus, trolley bus, tram and subway - it is a special case,or other types integrated into the system of city public transport (eg. shipping,funicular, etc.). Critical areas in this article, we mean those areas that maynegatively affect continuity and regularity of city public transport, in the worst caseof its alone operation. We acquainted with the critical areas in the operation of citypublic transport which may negatively affect the passenger, the carrier,and the company that operates this type of transport.
Keywords: city public transport; schedule; stopping distance